(untitled) (Research, Society and Development, 2021)
In Brazil, more than 70% of neonatal deaths are concentrated in the early neonatal period, with about 41.2% of them occurring in the first 24 hours of life. Thus, the objective of this study was to carry out an analysis of factors associated with early neonatal deaths that occurred in Sergipe, Brazil, through the linkage of records in the information systems: Live Birth Information System (SINASC) and Mortality Information System (SIM). This study was carried out in Sergipe, Brazil, in which an analysis was made of secondary data on children born and early neonatal deaths in Sergipe between 2006 and 2019 registered in the SINASC and in the SIM. A linkage was carried out between the databases, identifying 484,629 live births, 480,784 survivors and 3,845 who died with less than 7 days of life, with a low percentage of ignored data or absent. Maternal age was similar between groups. However, the newborns who died had lower weight, gestational age and Apgar in the first and fifth minutes than the survivor group. Regarding the newborn, there were more deaths in males and in congenital malformations. As for information about the mother and pregnancy, there were more deaths in single women, multiple pregnancies, lower gestational ages and vaginal delivery. There was an association between neonatal deaths and lower Apgar in the first and fifth minutes, lower weights, lower gestational ages, male gender, congenital malformations, women with multiple pregnancies, vaginal births and single mothers.